Stimulation of Innovation Activities in Service Areas - Hasanova, S. (Управління економікою: теорія та практика, 2022)
First of all, I would like to note that the realization of huge opportunities in the service sector makes them an important and intensively growing sector of the economy in the current conditions of agriculture. Representing an extremely important element and driving force of the world economic system, increasing opportunities for structuring social and economic development, the service sphere has become one of the strongest developing sectors of the economy, and currently contributes significantly to the creation of the country's GDP and the income of the population. Increasing its role in the local economy is a necessary priority of national development, a factor of maintaining the political and economic stability of the state in market conditions. A significant part of the service area is tourism, which is considered one of the largest, highly profitable and extremely dynamic sectors of the economy. Acting as an important factor of sustainable development and a business area against the background of globalization and activation of integration processes, tourism activity is formed by a set of numerous complex problematic reasons and management mechanisms and undergoes transformation in interaction.
Keywords: stimulation, innovation activities, service areas, mechanisms, transformation, interaction.

Lukianov A.I. Application of Integrated Logistics in Foreign Economic Business Processes of Enterprises of the Processing Industry. – Р. 163.
The article deals with the problems of efficient management of modern business processes, which require system optimization of interconnected circuits: the process of supply, production process, sales of products, and others. Presented modern concepts of business process management in the processing industry. The information concept of logistics is to formulate the general problem of managing material flows within an industry or a separate business process. The marketing concept of logistics focuses on the organization of the logistics process in the field of distribution and distribution of products. The concept of integrated logistics is to use in the management of a system tool to regulate material flows to achieve business goals. Перш за все, хотілося б відзначити, що реалізація величезних можливостей сфери послуг робить їх важливою та інтенсивно зростаючою сферою економіки в сучасних умовах сільського господарства. Будучи надзвичайно важливим елементом і рушійною силою світової економічної системи, збільшуючи можливості для структурування соціально-економічного розвитку, сфера послуг стала одним із найсильніших секторів економіки, що розвиваються, і на сьогодні робить значний внесок у створення ВВП країни та доходи населення. Підвищення її ролі в місцевій економіці є необхідним пріоритетом національного розвитку, фактором збереження політичної та економічної стабільності держави в ринкових умовах. Значну частину сфери обслуговування займає туризм, який вважається однією з найбільших, високоприбуткових і надзвичайно динамічних галузей економіки. Виступаючи важливим чинником сталого розвитку та бізнес-сферою на тлі глобалізації та активізації інтеграційних процесів, туристична діяльність формується комплексом численних складних проблемних причин і механізмів управління та зазнає трансформації у взаємодії.